Microbiological effectiveness of household water treatment technologies under field use conditions in rural Tanzania. Issue 1 (19th November 2015) - Mohamed, Hussein; Clasen, Thomas; Njee, Robert Mussa; Malebo, Hamisi M.; Mbuligwe, Stephen; Brown, Joe
Abstract: Objectives: To assess the microbiological effectiveness of several household water treatment and safe storage (HWTS) options in situ in Tanzania, before consideration for national scale‐up of HWTS. Methods: Participating households received supplies and instructions for practicing six HWTS methods on a rotating 5‐week basis. We analysed 1202 paired samples (source and treated) of drinking water from 390 households, across all technologies. Samples were analysed for thermotolerant (TTC) coliforms, an indicator of faecal contamination, to measure effectiveness of treatment in situ . Results: All HWTS methods improved microbial water quality, with reductions in TTC of 99.3% for boiling, 99.4% for Waterguard ™ brand sodium hypochlorite solution, 99.5% for a ceramic pot filter, 99.5% for Aquatab ® sodium dichloroisocyanurate (NaDCC) tablets, 99.6% for P&G Purifier of Water ™ flocculent/disinfectant sachets, and 99.7% for a ceramic siphon filter. Microbiological performance was relatively high compared with other field studies and differences in microbial reductions between technologies were not statistically significant. Conclusions: Given that microbiological performance across technologies was comparable, decisions regarding scale‐up should be based on other factors, including uptake in the target population and correct, consistent, and sustained use over time.